SINERGI DIGITALISASI UMKM DAN INOVASI PRODUK SABUN CUCI PIRING DALAM MENINGKATKAN KEMANDIRIAN EKONOMI MASYARAKAT (STUDI KASUS DI DESA EMPUS KABUPATEN LANGKAT) - Putri Elda Sari; Lyra Nadia Srg; Edo Adrio; Abdurrahman; Siti Aisyah (Jurnal Pengabdian Masyarakat Sabangka, 2026)
The Community Service Program in Empus Village, Langkat Regency, aims to increase the community's economic independence through the MSME Digitalization and Dishwashing Soap Product Innovation program. This program focuses on strengthening the capabilities of micro, small, and medium enterprises (MSMEs) in utilizing digital technology and providing practical training in making household products with economic value. The implementation method includes outreach, mentoring, and skills training. The results of the activity show that digitalization has increased MSMEs' understanding of the importance of online marketing through e-commerce and Google Maps, although some business owners are still adapting. Meanwhile, the dishwashing soap production training produced approximately 30 250 ml bottles and provided new skills for village mothers to develop their household businesses. Overall, this activity effectively fosters an entrepreneurial spirit, strengthens digital literacy, and supports village economic development based on sustainable innovation.